PENGEMBANGAN KURIKULUM PAI YANG BERBASIS MULTIKULTURAL - Khairul Hammy (LP2M STAI Darul Kamal NW Lombok Timur, 2016)
Conflicts and disputes wearing a religion is often the case, terrorist acts, arson and destruction of facilities and places of worship, and still suspicion suspect between Muslims and Christians and other religions in our country. It’s enough to prove the failure of the process of religious education all this time. Although many efforts have been made by the experts and religious leaders to create the cordial and harmonious relations among religious communities, in Indonesia the country's notoriously of pluralistic. To obtain success for the realization of the noble objectives, and the form of peace and brotherhood lasting among our society which in reality have different religion and faith, presumablyit is necessary the courage to invite them to make changes in education, particularly through curriculum-based diversity. Innovation and development of Religious Education curriculum needs to be done because of the nature of the curriculum is dynamic, always changing and adjusting to needs. Because the learning environment is a pluralistic society, the renewal and development of curriculum should be based PAI diversity by displaying the tolerant face of Islam. Curriculum development and innovation can be explained from the standpoint of perrenialismphilosophy, essentialism and progressivism. From this it is possible to teach the principles of Islam humane, democratic and fair to students. A principles of Islam that is very relevant to enter the future world marked by cultural and religious diversity.